An Easily Accessible Self‐Healing Transparent Film Based on a 2D Supramolecular Network of Hydrogen‐Bonding Interactions between Polymeric Chains. Issue 38 (25th May 2016) - Roy, Nabarun; Tomović, Željko; Buhler, Eric; Lehn, Jean‐Marie
Abstract: Self‐healing polymers hold great promise for the future, enhancing in particular the longevity of polymeric materials. We describe a self‐healing covalent polymer, presenting an extensive array of hydrogen‐bonding sites based on the combination of urea, urethane, and bis‐acyl‐hydrazine units. Solvent‐cast thin‐films prepared by polycondensation of a commercially available dihydrazide and a diisocyanate prepolymer exhibited excellent room temperature autonomous healing with almost full recovery of mechanical properties when two parts of a cut film were overlapped and gently pressed together. This autonomous healing upon damage may be attributed to the supramolecular dynamics of multiple lateral inter‐chain hydrogen‐bonding interactions between the polymer chains. The solid‐state structure of a model compound incorporating the same structural backbone corroborates the existence of an extensive two‐dimensional supramolecular hydrogen‐bonding network. Abstract : Healing bonds : A self‐healing covalent polymer, presenting an extensive array of hydrogen‐bonding sites based on the combination of urea, urethane, and bis‐acyl‐hydrazine units is described (see scheme).